Determinants of household cooking fuel choices in India - Preeti (IISERM, 2020)
This study attempts to understand the factors that drive the adoption of cleaner cooking fuels in rural Punjab and Haryana. We find that family size is an important determinant of per capita cooking fuel consumption. Larger families consume less cooking energy than smaller families. Smaller families generally tend to have average sized pots whereas bigger families need bigger pots and utensils, which consume less energy when consumption is normalized to the amount cooked. Hence more energy is needed to cook the food for a person living in a small family and more wastage tends to occur with individuals and small families. The drop in the per capita cooking energy consumption with increasing family size is called the economy of scale. While studying stove stacking behavior we find that landowning families with lower disposable income use more biofuel and less LPG whereas those with more disposable income use less biofuel and more LPG. LPG and biofuel consumption are inversely related to each other. This indicates that in cases where biofuel is available and free, income becomes an important driver of fuel choices. The increase of LPG energy usage for landowning families with larger cooling bills somehow satisfies the concept of ‘energy ladder theory’. This theory proposes that increase in income leads to people leaving traditional fuels and moving to modern clean fuels. For landless families both biofuel and lpg consumption appear to be independent of the disposable income, however, the average LPG and biofuel cooking energy consumption of households are inversely related to each other. This interesting phenomenon deserves further study. Landless families appear to violate the ‘energy ladder theory’ showing that increasing income does not necessarily lead to adoption of clean cooking fuels, while even those with little disposable income can adopt clean cooking fuels. It is possible that parameters not recorded such as cattle ownership which results in free access to cow dung cakes impact the cooking fuel choices of landless families. The landless families without cattle, have to pay for their cooking fuel in any case, even if they buy firewood or dung cakes. So if the prices of LPG is cheap, those who anyways have to buy their fuel, might chose to switch to the more convenient LPG fuel.
Keywords: cooking fuels; India; rural; Punjab; Haryana